Evaluating the efficacy of seasonal grazing and livestock exclusion as restoration tools for birds in riparian habitat of the Okanagan Valley, British Columbia, Canada. Issue 5 (19th January 2017) - Forrester, Timothy R.; Green, David J.; McKibbin, René; Bishop, Christine A.
Abstract: Riparian habitat supports the highest density and diversity of songbirds in Western North America despite covering less than 1% of the land area. Widespread destruction and degradation of riparian habitat, especially by livestock grazing, has led to habitat restoration efforts. In 2000, restoration activities in the form of permanent and seasonal exclusion of livestock from riparian areas were initiated to improve habitat for the endangered Western Yellow‐breasted Chat ( Icteria virens auricollis ) population, which is dependent on early successional shrub habitat for nesting, in the Okanagan Valley of British Columbia, Canada. We assessed the effectiveness of livestock exclusion by examining temporal changes in the abundance, richness, and breeding performance of birds in restoration and reference sites. The abundance of W. Yellow‐breasted Chats significantly increased between 2002 and 2013 in areas where restoration activities occurred. However, restoration did not have significant effects on the abundance, richness, or breeding performance of other riparian birds at the restoration sites independent of temporal changes that occurred at reference sites. Our results provide evidence that limiting livestock grazing in temperate riparian areas can lead to recovery of endangered riparian songbirds that rely on early successional shrub habitat but may have limited effects on common species that are not strictly reliant on this habitat.